Analisis Dan Perancangan Sistem Informasi Laporan Kinerja Harian Dosen Dengan Pendekatan Object-Oriented Dan Agile Unified Process (AUP) - Rio Irawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The lecturer's daily performance report is a recording of activities carried out by a lecturer every working day and then reported once a year to the staffing department at the Palangka Raya State Islamic Institute (IAIN) as one of the bills for lecturers who receive performance allowances. The contents of this report generally consist of Tri Dharma activities carried out by the lecturer concerned, including teaching, researching, and community service activities. Based on this, a web-based system was designed that was used to record daily performance reports by lecturers and verify lecturers' daily performance data that had been submitted by the lecturer. The system will handle the daily performance reporting of lecturers in real-time which can be directly verified by the verifier to produce data with a better level of validity. The analysis and design are carried out with an object-oriented approach using the Unified Modeling Language (UML), while the software engineering method used is Agile Unified Process (AUP) model.